Du Buzz Blades au « Discozigzag » : traduire en français les armes loufoques de Ratchet & Clank - Alice Ray (ReS Futurae)
Science fiction is a genre that doesn't lack humor and video games also embrace this unrestrained, self-referential subgenre of science fiction that loves to play with its own conventions. In 2002, the first installment of the Ratchet & Clank series was released on PS2 (by Insomniac Games), offering a cartoonish, whimsical sci-fi world. This world was revisited in a remake of the same name in 2016 on PS4, featuring just as many (if not more) science-fictional terms. The translator’s challenge is threefold: to preserve the sci-fi nature of the terms, to retain their humorous qualities, and to create terms that are coherent with the objects' effects in the game world. This article offers a contrastive analysis of the weapons’ names in English and French across the two versions of Ratchet & Clank, using the concept of “generic fluency” (Korpi, 2017) and prior research on lexical creations in English and French (Angenot, 1979; Gindre, 1999; Poix, 2020), to examine how the three aspects—science fiction, humour, and interaction—were conveyed in the French versions of these games and to shed light on the translators' choices. The existence of a remake also allows for an examination of any evolution between 2002 and 2016, whether in the original language’s lexical creations or in their translation.